Home of Hope a drug treatment and rehabilitation center for women - Redublado, Kaseelyn L. (College of Architecture, University of the Philippines Diliman, 2017)
Home of Hope : A Drug Treatment and Rehabilitation Center for Women is a project proposal for the local government of Quezon City. It will be located in Barangay Payatas to address the social issues on drugs and lack of livelihood due to closure of Payatas Dumpsite, and to foster recycling, as well. It aims to give hope to the drug abusers, to the unemployed, and to things that are seemingly indispensable. The project will be a rehabilitation center for women that will include aftercare services such as skill development training and livelihood programs. The livelihood program will be built on the capabilities and strengths of the community: therefore, this will focus on recycling. Moreover, the project sill serve as an extension of the Quezon City Drug Treatment and Rehabilitation Center (TAHANAN), which is a priority project of the local government of Quezon City based on their Comprehensive Development Plan (CDP) and the City Development and Planning Office. Furthermore, the project will translate the concept of Hope, specifically, through therapeutic architecture (light and kinesthesia) to provide overall healing to the residents of the rehabilitation center, and to help them reintegrated into the community after the treatment and rehabilitation.